2022
DOI: 10.3390/antiox11071410
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Donor GYY4137 Rescues NRF2 Activation in Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) can cause severe respiratory illness in infants, immunocompromised, and older adults. Despite its burden, no vaccine or specific treatment is available. RSV infection is associated with increased reactive oxygen species (ROS) production, degradation of the transcription factor nuclear factor erythroid 2-related factor 2 (NRF2), and decreased antioxidant enzymes (AOEs), leading to oxidative damage and lung injury. Hydrogen sulfide (H2S) is an endogenous gaseous molecule that pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…On the other hand, the administration of steroids, an anti-inflammatory medication, has been shown to reduce the level of severity [ 7 , 38 , 42 ]. In addition, other reports have noted that the administration of antioxidants resulted in reductions in inflammation and severity in respiratory viral infection cases [ 43 , 44 , 45 ], with similar effects expected in patients affected by COVID-19 [ 5 , 34 ]. Additionally, uric acid has been shown to gain an antioxidant property by scavenging ROS, such as singlet oxygen, and peroxyl and hydroxyl radicals, and is also known to provide approximately half of the free radical-scavenging capacity in the human body [ 8 , 46 ].…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, the administration of steroids, an anti-inflammatory medication, has been shown to reduce the level of severity [ 7 , 38 , 42 ]. In addition, other reports have noted that the administration of antioxidants resulted in reductions in inflammation and severity in respiratory viral infection cases [ 43 , 44 , 45 ], with similar effects expected in patients affected by COVID-19 [ 5 , 34 ]. Additionally, uric acid has been shown to gain an antioxidant property by scavenging ROS, such as singlet oxygen, and peroxyl and hydroxyl radicals, and is also known to provide approximately half of the free radical-scavenging capacity in the human body [ 8 , 46 ].…”
Section: Discussionmentioning
confidence: 75%
“…Most of these ROS-mediated cellular events seem to do more harm than good in RSV infection. Substantial evidence has shown the beneficial effects of antioxidant treatment in severe RSV infection, such as inhibition of RSV replication and improvement of barrier dysfunction and lung inflammatory injury [ 15 , 50 , 62 , 163 , 165 ]. In addition, zinc is a stable divalent cation and does not directly undergo redox reactions, but it is involved in regulating the oxidant/antioxidant balance [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulating the expression of Nrf2 and AOEs can reduce RSV infection in human lung epithelial cells and mitigate RSV-induced injury and oxidative stress in mice [ 53 , 61 ]. A recent study indicated that the H 2 S donor GYY4137 decreases Keap1 levels and modulates pathways involved in RSV-induced Nrf2 degradation, contributeing to the significantly increased Nrf2 levels and AOE gene expression, which could be explored as a potential therapeutic application in RSV infection [ 62 ].…”
Section: Oxidative Stress and Enhanced Ros Production During Rsv Infe...mentioning
confidence: 99%
“…In addition, we do not know how H 2 S decreases the DNMT1 mRNA level. mRNA production is regulated by transcription factors and transcription repressors, and H 2 S can regulate the expression of transcription factors [ 50 , 51 ]. Considering H 2 S decreases the DNMT1 protein level via limiting its mRNA, we think H 2 S regulates DNMT1 at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%